PEMBINAAN PEGAWAI NEGERI SIPIL PADA DINAS PENDIDIKAN KABUPATEN PIDIE (Studi Implimentasi Peraturan Pemerintah Nomor 12 Tahun 2002 Tentang Kenaikan Pangkat Pegawai Negeri Sipil) - Halimah Halimah (Jurnal Sosial Humaniora Sigli, 2020)
The existence of government employees was a crucial thing in doing the government assignment and development within government organizations. In this case, the government needed professional, strong, responsible, friendly and impersonal employees through coaching conducted base on job and performance career system. Pidie District Education offices needed some steps in developing education was suitable with the job and performance system for realizing a good government employees. The development done was based on the 34th constitution, 12th subsection and 1st verse in 1999 about constitution amendment of the 8th in 1974 about the employees affair that sound was “the government employees management was encouraged to certify the government assignment and development efficiently”. Hence, it needed construction continuously from recruitment process became an employee until she/he became pension. It aims to certify the assignment continuously. The aim of the study was to describe and analyze the construction of the government employees on the Pidie District Education Offices and resistor and support factors in developing the government employees. The method of the study was qualitative research by conducting the prime and secondary data were larger. It covered the legal document issued by the government such as the government employee constitution and the expert opinion. Data collection conducted by doing library and documentation research. Data analysis was performed by descriptive analysis, those were: data reduction, display and conclusion/verification. From the research result could be concluded that the process of advancement of the government employees were to get structural position which were still have weaknesses in arranging constructing system or locating a structural position within government bureaucracy. Consequently, it needed firmness in arranging government employees lifting mechanism in structural position. Key Words: Employees, advancement